2020
DOI: 10.3390/ijms21062174
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of NO and H2S in Sperm Biology: Recent Advances and New Perspectives

Abstract: After being historically considered as noxious agents, nitric oxide (NO) and hydrogen sulfide (H2S) are now listed as gasotransmitters, gaseous molecules that play a key role in a variety of cellular functions. Both NO and H2S are endogenously produced, enzymatically or non-enzymatically, and interact with each other in a range of cells and tissues. In spite of the great advances achieved in recent decades in other biological systems, knowledge about H2S function and interactions with NO in sperm biology is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 137 publications
0
15
0
Order By: Relevance
“…Actually, such measurement is attributable to the crucial role of nitric oxide in regulation of sperm motility. In fact, various studies have confirmed the presence of nitric oxide synthase in human spermatozoa and seminal plasma (O'Bryan et al., 1998), and nitric oxide has been identified as a vital modulator in maintaining the adequate motility of the spermatozoa (Banihani, 2020; Banihani et al., 2018; Donnelly et al., 1997; Kadlec et al., 2020). As a result, there was insignificant decrease in the level of nitric oxide produced in the presence of caffeine at all tested concentrations except for the 20 mM concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, such measurement is attributable to the crucial role of nitric oxide in regulation of sperm motility. In fact, various studies have confirmed the presence of nitric oxide synthase in human spermatozoa and seminal plasma (O'Bryan et al., 1998), and nitric oxide has been identified as a vital modulator in maintaining the adequate motility of the spermatozoa (Banihani, 2020; Banihani et al., 2018; Donnelly et al., 1997; Kadlec et al., 2020). As a result, there was insignificant decrease in the level of nitric oxide produced in the presence of caffeine at all tested concentrations except for the 20 mM concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the selection of these parameters is attributable to their vital role in maintaining the adequate motility of spermatozoa. For example, various studies have shown that nitric oxide synthase is present in human spermatozoa (O'Bryan et al., 1998) and that nitric oxide modulates the maintenance of adequate motility of the spermatozoa (Banihani, 2020; Banihani et al., 2018; Donnelly et al., 1997; Kadlec et al., 2020). Change in the levels of endogenous nitric oxide produced was found to significantly affect sperm motility (Donnelly et al., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S, their main precursor, has been related to normal erectile function and sperm motility at physiological levels, while its insufficiency has been implicated in impaired spermatogenesis and blood-testis barrier defects. Excessive RSS levels may also be detrimental to sperm movement owing to low energy levels caused by the inhibition of mitochondrial electron transport and ATP generation [28].…”
Section: Redox Balance Implies Moderation-"μέτρον"mentioning
confidence: 99%
“…Hand-searched/Reference list checked 29 [9,10,27,28,31,34,42,47,[49][50][51][52][53][54][55][58][59][60][61][63][64][65][66][67]69,70,81,82,87]…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The importance of nitric oxide (NO) and hydrogen sulfide (H 2 S) in male reproduction has been widely recognized [ 1 , 2 , 3 , 4 , 5 ]. Together with carbon monoxide (CO), the members of the gasotransmitter family participate not only in spermatogenesis, but also in epididymal sperm maturation [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%